2022
DOI: 10.3390/ijerph192316034
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Activity, Sedentary Behavior, Satisfaction with Sleep Fatigue Recovery and Smartphone Dependency among Korean Adolescents: An Age- and Gender-Matched Study

Abstract: The purpose of this study was to identify the association between physical activity (PA), sedentary behavior (SB), satisfaction with sleep fatigue recovery (SSFR), and smartphone dependency in South Korean adults. We analyzed data from the National Health and Nutrition Examination Survey 2020 data. We selected participants who answered Internet addiction-related questions as “Very much” (n = 241) and answered Internet addiction-related questions as “Not at all” (n = 241) in the questionnaire. The participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…Additionally, the mediating effect of smartphone dependency, as revealed in our study, highlights the potential to use exercise as a method to reduce this dependency. While numerous studies emphasize the detrimental effects of increasing smartphone dependency on adolescent mental health [13,16,18], emerging research suggests that physical activity may be employed to mitigate this dependency [25,27]. In particular, this aligns with research results indicating that aerobic exercise interventions reduced the desire for mobile phone use among university students with high mobile phone dependency [33] and identifying that exercise negatively predicted smartphone addiction [34].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Additionally, the mediating effect of smartphone dependency, as revealed in our study, highlights the potential to use exercise as a method to reduce this dependency. While numerous studies emphasize the detrimental effects of increasing smartphone dependency on adolescent mental health [13,16,18], emerging research suggests that physical activity may be employed to mitigate this dependency [25,27]. In particular, this aligns with research results indicating that aerobic exercise interventions reduced the desire for mobile phone use among university students with high mobile phone dependency [33] and identifying that exercise negatively predicted smartphone addiction [34].…”
Section: Discussionmentioning
confidence: 66%
“…For instance, a study identified that the physical activity levels of university students negatively and directly predicted smartphone dependency [25,26]. Another study suggests that as adolescents engage in more moderate-to vigorous-intensity physical activities, their smartphone dependency may decrease [27]. Given the lack of a clear understanding of the relationship between problematic smartphone usage and physical activity, it is necessary to investigate these two variables for the enhancement of adolescent mental health.…”
Section: Introductionmentioning
confidence: 99%
“…People's self-control, like muscles, has an upper limit, when beyond this limit, people's behavior is easy to get out of control [33][34][35]. According to the theory of limited self-control, the loss of self-control will lead to the decline of college students' ability to resist hedonistic experiences, so they are prone to internet addiction [36,37]. The basic explanation of the loss of compensation hypothesis for internet addiction is that internet rational compensation leads to loss of compensation and Internet addiction behavior [38].…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO's 2020 catalog of PA recommendations, sedentary behavior in children can be associated with various health issues: "increased adiposity; poorer cardiometabolic health, fitness, behavioural conduct/pro-social behaviour; and reduced sleep duration" [4]. Usually, smartphone usage is classified as sedentary behavior [10,11], and children are suggested to limit their screen time. Location-based games that promote outdoor activities (like KIJANI, the game proposed in this research) could change that narrative.…”
Section: Introductionmentioning
confidence: 99%